Design and development of filter and antennas integrations at 2.45 GHZ for wireless local area network (WLAN) applications - Butt, Muhammad Shoaib (2020)
This thesis presents design and development of filter and antennas integrations at 2.45 GHz for WLAN applications. Antenna and band pass filter are two main components of RF front end systems. Due to long transmission path, the losses between the antenna and bandpass filter affect the performance of the overall RF systems. To reduce the losses and to reduce the size of the RF front end system, these two components are integrated to a single structure that has both the filtering and radiating properties. Two filtering antennas namely Design 1 and Design 2 are proposed. Design 1 is the integration of hairpin band pass filter and micro strip patch antenna. Design 2 is the integration of hairpin band pass filter and dipole antenna. The methodology used to design the filtering antennas is the filter synthesis method. In this method the last stage of the hairpin band pass filter is replaced/merged with the antenna. All designed structures were simulated using Computer Simulation Technology (CST) Microwave studio. The main advantage of the filter synthesis method is that the resulting structure has reduced size and more suited for narrow band antennas. Other advantages include sharp selectivity and good out of band gain suppression. In order to compare the performances of Design 1 and Design 2 their performances are compared to conventional patch and dipole antennas. Simulation results show that design 1 has achieved a size reduction of 35 % compared to cascaded structure of bandpass filter with patch antenna whereas design 2 has achieved a size reduction of about 25 % compared to cascaded bandpass filter with dipole antenna. The filtering antennas are successfully designed, simulated and optimized for the WLAN applications.